Implementasi Mata Pelajaran Akidah Akhlak dalam Pembentukan Karakter Siswa Madrasah Ibtidaiyah Negeri 3 Tapanuli Tengah - Sapirin Sapirin; Adlan Adlan; Candra Wijaya (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2019)
Character education is understood as an effort to instill intelligence in thinking, appreciation in the form of attitudes, and experiences in the form of behavior that is in accordance with the noble values that are the identity of themselves. Character education instilled in Islamic education is the creation of the nature of students who have moral character. The importance of character education because some of the problems of the current generation are moral crises. The research method used in qualitative research with field research uses a descriptive approach. Based on the data analysis found The form of character education material in moral akidah learning at MIN 3 Middle Tapanuli requires teaching, exemplary, and reflection of morals, worship, and aqeedah. The most important points in character education teach children to behave according to the guidance of the Koran and the Sunnah. Implementation of Character Education in moral learning in MIN 3 Central Tapanuli is carried out in three ways, namely learning activities in the classroom, activities outside the classroom, and activities outside of school. Existing facilities and infrastructure are recognized or not have helped provide convenience in character education in moral akidah learning at MIN 3 Central Tapanuli with existing materials and using methods of habituation, exemplary, and reflection as well as methods that activate students in the process learning.